Programa educativo de estrategias metacognitivas para mejorar el aprendizaje autónomo en estudiantes de práctica pre profesional de la facultad de Ciencias De La Educación y Humanidades Universidad Nacional de la Amazonía Peruana Iquitos 2021 - López Alvarado, Linda Priscilla (2024)
The main objective of the study was to evaluate the effect of an educational program of metacognitive strategies to improve autonomous learning in preprofessional practice students of the FCEH UNAP, Iquitos, 2021. An evaluative type of research was used, with a quasi-experimental design of two groups with pre-test and post-test, univariate and longitudinal. The sample consisted of 60 students, 30 in the experimental group and 30 in the control group. A performance test validated by experts was applied as a data collection instrument. The results showed that the educational program of metacognitive strategies was effective to improve autonomous learning, since in the post- test an increase in the percentage of students in the high level and a decrease in the percentage of students in the low level was observed, compared to the pretest. Thus, the general hypothesis of the research was verified.